Produksi Karbon Aktif dari Cangkang Sawit dan Aplikasinya Pada Penyerapan Zat Besi, Mangan Dan ph Air Sumur - Vera Viena; Bahagia Bahagia; Zairi Afrizal (Fakultas Teknik, 2020)
Most of the solid waste from Palm oil Industry in Indonesia has not been exploited optimally to become valuable product. This research aims to produce activated carbon from palm oil shell waste and applied it for the adsorption of Fe, Mn and pH of shallow well. Production of Palm shell activated carbon (PSAC) were done under following steps; e.i palm shell preparation, oven dried, carbonization at 400 0C, dan then activated at 600 0C. PSAC Characterization conducted based on Indonesion Standard of SNI No.06-3730-95, which consist of water content, ash content, fly ash content and fixed carbon, while surface of PSAC analized using FTIR method. Shallow well sampling were taken from 2 wells from Drien Tujoh Village, Nagan Raya District. PSAC contacted time varied from 30-120 minute. The highest PSAC adsorption efficiency were obtained both at 120 minute contacted time, which range from 10,41 - 58,34% for Fe(II); 9,51 - 48,90% for Mn(II) and pH raised from 5,8 to 7,6. In conclusion, the PSAC product has been able to remove Fe, Mn and pH content in accordance with water quality standard published by Indonesian Government, and it could be marketed for increasing the people’s income.